The Effect of Liquidity and Solvency on Company Value With Profitability as a Mediating Variable - Chella , Chella; Purnama, Eka Desy (Goodwood Publishing, 2026)
Purpose: This study examines the effect of liquidity and solvency on firm value, with profitability as a mediating variable, using empirical evidence from PT Panca Budi Idaman Tbk during the 2017–2024 period. Research methodology: This study employs a quantitative approach using secondary data from the company’s published financial statements. Liquidity is measured by the Current Ratio, solvency by the Debt to Equity Ratio (DER), profitability by Return on Assets (ROA), and firm value by Tobin’s Q. Data are analyzed using multiple linear regression and mediation analysis, supported by classical assumption tests and the Sobel test. Results: The results show that liquidity has a positive and significant effect on profitability, while solvency has a negative and significant effect on profitability. Profitability positively and significantly affects firm value. Liquidity also has a positive and significant direct effect on firm value, whereas solvency does not have a significant direct effect. Mediation analysis confirms that profitability significantly mediates the relationship between liquidity and firm value, as well as between solvency and firm value. Conclusions: The study concludes that profitability plays a key mediating role in transforming liquidity conditions and capital structure decisions into higher firm value, supporting signaling theory that strong financial performance sends positive signals to the market. Limitations: The study is limited to a single listed company and selected financial ratios, which may restrict generalizability. Contribution: This research contributes empirical evidence on profitability as a mediating mechanism linking liquidity and solvency to firm value and provides practical insights for managers and investors.